Analisis ANALISIS PENDALAMAN MATERI AL-QUR'AN HADIS DALAM PEMBELAJARAN KONTEKSTUAL DI MADRASAH TSANAWIYAH - Ahmad Abrani Noor; Mahyuddin Barni (PT. Sulthan Journal Publisher, 2026)
Al-Qur'an Hadith learning in Islamic Junior High Schools (Madrasah Tsanawiyah) continues to face challenges due to the predominance of memorization-oriented and textual approaches, which limit students’ ability to relate Qur'anic verses and Hadith to real-life contexts. This study aims to analyze the enrichment of Al-Qur'an Hadith materials through contextual learning as an effort to create more meaningful and relevant learning experiences. The study employed a library research method by reviewing books, scholarly articles, curriculum documents, and previous studies related to Al-Qur'an Hadith instruction and contextual learning. Data were analyzed using content analysis to identify concepts, strategies, and implications of contextual learning in material enrichment. The findings reveal that contextual learning shifts the orientation of instruction from mere text mastery toward deeper, reflective, and applicable understanding. By connecting learning materials with students’ real-life experiences, the values and messages of the Qur'an and Hadith become easier to understand, internalize, and implement in everyday life. Therefore, contextual learning contributes to improving the quality of Al-Qur'an Hadith education by emphasizing not only cognitive achievement but also the development of attitudes and behaviors in accordance with Islamic teachings.